2020
DOI: 10.3390/ma13194375
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Wheat Straw Pellets Individually and in Combination with Cassava Starch or Calcium Carbonate under Various Compaction Conditions: Determination of Pellet Strength and Water Absorption Capacity

Abstract: This study aimed to optimise the production conditions of wheat straw (WS) pellets and pellets with the additives of cassava starch (CS) or calcium carbonate (CC) based on the criteria of pellet strength and water absorption by crushed pellets. The pellets produced using a 2–10%-wt/wt additive ratio, material moisture of 10–30% w.b., die height of 66–86 mm, and material temperature of 78–108 °C were tested. The influence these factors on the strength parameters of pellets was different than on the water absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to Matkowski et al [12] and Nath et al [38], who studied the process of straw pelleting with various additives, the optimal range of moisture content for the pelleted mixture was approximately 18-20% due to the formation of durable pellets with the highest bulk density and kinetic strength. Niedziółka et al [37], who examined the process of the pelleting of wheat, rapeseed, and corn straw, indicate that the optimum range of moisture content for the pelleting of material is 18-22%.…”
Section: Moisture Of Tested Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Matkowski et al [12] and Nath et al [38], who studied the process of straw pelleting with various additives, the optimal range of moisture content for the pelleted mixture was approximately 18-20% due to the formation of durable pellets with the highest bulk density and kinetic strength. Niedziółka et al [37], who examined the process of the pelleting of wheat, rapeseed, and corn straw, indicate that the optimum range of moisture content for the pelleting of material is 18-22%.…”
Section: Moisture Of Tested Materialsmentioning
confidence: 99%
“…Matkowski et al [12] pelleted wheat straw with the addition of cassava starch and calcium carbonate. They concluded that unit compaction work, relative to dry matter, was the highest for wheat straw without additions, i.e., 18.1 kJ•kg −1 .…”
Section: Pellets Density and Bulk Density Of Pelletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum strength of spruce pellets (higher than 10 N/mm) was found at MC of 8.3% (at pressure of 300 and 400 MPa) [45]. Another study found the maximum strength of 2.68 MPa for wheat straw pellets at MC of 23.2% [71]. Mohammad Ramezanzade et al [72] recommended the MC of 11.7%, particle size of 1.65 mm and temperature of 100 o C for obtaining the higher quality of biomass pellets (i.e.…”
Section: Pellet Quality Comparison With Previous Studiesmentioning
confidence: 91%